2000
DOI: 10.1111/j.1523-1755.2000.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputed tomography of kidneys following chronic bile duct ligation

Abstract: The results indicate that after CBDL, there is a selective decrease in cortical vascular filling, which may contribute to the salt and water retention that accompanies cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…[25][26][27][28] In addition, the implementation of quantitative analyses of 3D vascular networks revealed a previously unrecognized reduction of vessel branches during disease progression paralleled by increased tortuosity of the remaining vessels. Extending previous studies, [51][52][53] we found that not only post-glomerular vessels, i.e., capillaries, but all large-to-small-sized blood vessels in the kidney exhibited substantially reduced luminal diameters during disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] In addition, the implementation of quantitative analyses of 3D vascular networks revealed a previously unrecognized reduction of vessel branches during disease progression paralleled by increased tortuosity of the remaining vessels. Extending previous studies, [51][52][53] we found that not only post-glomerular vessels, i.e., capillaries, but all large-to-small-sized blood vessels in the kidney exhibited substantially reduced luminal diameters during disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on Microfil perfusion of the renal vasculature in mice and rats. [25][26][27][28] Here, we used this highresolution ex vivo mCT method to analyze vessel morphometrics that can be derived from perfused renal vasculature, such as branching, size and tortuosity, in progressive kidney fibrosis.…”
Section: Peritubular Capillary Rarefaction Correlates With Fibrosis Imentioning
confidence: 99%
“…To prepare rat kidneys for micro-CT, the blood is flushed from renal vasculature at physiological pressure with an infusion of heparinized 0.9% saline (37,69). The infusion is continued with a formalin solution to fix the tissue, and the free formalin is flushed from the kidneys with a saline solution.…”
Section: Preparation Of Tissue For Micro-ctmentioning
confidence: 99%
“…However, previous information has not been available in regards to microvessel density in renal tissue during the hypertension. To measure the changes in microvasculature, we used micro-CT, which provides a means to obtain quantitative volumetric information (6,15,22). NO is an important physiological antagonist of vasoconstrictors such as ANG II.…”
Section: Discussionmentioning
confidence: 99%
“…Losartan was used to determine the role of AT 1 receptors. To examine and measure the changes in renal vasculature, we used a three-dimensional X-ray microcomputed tomography (micro-CT) system (6,15,22). These changes were further evaluated by histological examination.…”
mentioning
confidence: 99%